Toxic Release Consequence Analysis for Inherently Safer Design - Chang, Louis Hou Wei (Universiti Teknologi PETRONAS, 2016)
Safety is often one of the biggest concern in the designing a plant. Any engineering mistake or carelessness can be fatal and lead to unimaginable consequences. Bhopal accident of year 1984, Flixborough accident in year 1974, Seveso accident (1976), all of them are once the worst engineering nightmares and the effects are still haunting up until today. Based on the reported accidents in the past, toxic release is reflected as major accidents that has high fatality rate and relatively long catastrophic effect. In order to reduce the risk in the plant, commonly the add-on protective features will be installed after process design stage. However, this installation will increase the cost of the plant and it does not eliminate the hazard. In this project, another plant design approach is introduced with the emphasis on inherent safety concept